Bibliometric Analysis of Arabic Proficiency based on Scopus-Indexed Articles - Yunita Yunita; R. Umi Baroroh Baroroh; Sri Utami; Yulianingsih Riswan; Ike Fitriana Saraswati (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This study examined the evolution of research on Arabic language competency, including which nations have made substantial contributions, what topics come up regularly, and what research subjects are available to those interested in the discipline. This research is a bibliometric analysis on academic papers dealing with Arabic speaking skills. The total of 155 articles are collected from the Scopus website, then uploaded to the biblioshiny application using R-studio Cloud. All information is extracted to CSV format for data analysis and then entered the VOS viewer. The results show that (1) due to historical reasons and proximity to the Arabic language, Israel is the country with the largest number of authors on "Arabic speaking proficiency", followed by Egypt; (2) the keywords that often appear in articles on Arabic speaking proficiency are "phonological awareness", "diglossia", and "literacy"; (3) in general, the trend of the quantity of publications on the themes studied is increasing from year to year, indicating the growing interest of academics on the topic being discussed; (4) based on theme mapping, the dominant linguistic-related keywords in relation to the issue are also very open to being associated with other aspects such as SES (socioeconomic status), dyslexia, diglossia, and bilingualism.